1972
DOI: 10.1111/j.1600-0722.1972.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dental health data obtained from questionnaires, interviews and clinical examination

Abstract: – Validity of response to a postal questionnaire, answered by 216 persons, was studied by comparing data from the respondents on the occurrence of dentures and on the number of remaining teeth with data recorded by a clinical examination. Information, collected in a personal interview on gingival disease, was compared with clinical records. Reliability was studied by examining the agreement between data from the questionnaires and from the interviews concerning time interval since the last dental visit. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
72
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 2 publications
9
72
0
Order By: Relevance
“…The validity and reliability of the questions used in this study have been tested in earlier studies (Heloe, 1972;Ahlstrom-Laakso, 1975;Norheim and Heloe, 1977;Honkala, 1984), and the possible factors causing bias were wellj Dent Res 76 (9) controlled in this study design (see "Materials and I…”
Section: Discussionmentioning
confidence: 99%
“…The validity and reliability of the questions used in this study have been tested in earlier studies (Heloe, 1972;Ahlstrom-Laakso, 1975;Norheim and Heloe, 1977;Honkala, 1984), and the possible factors causing bias were wellj Dent Res 76 (9) controlled in this study design (see "Materials and I…”
Section: Discussionmentioning
confidence: 99%
“…1,2 There have also been a variety of self-reporting methods used for periodontal conditions. 2,[3][4][5][6][7] The range of information gathered in studies of self-reported periodontal health varies. Helöe asked people if they had ever had 'gum disease' after some common symptoms of gingival inflammation had been explained to them.…”
mentioning
confidence: 99%
“…Helöe asked people if they had ever had 'gum disease' after some common symptoms of gingival inflammation had been explained to them. 2 This was compared with gingival conditions scored according to the Gingival Index of Löe and Silness. 8 Brunswick and Nikias had adolescent patients rate their gum condition on a scale ranging from excellent to poor and compared this with an assessment made by a dentist of the same persons' overall oral health, 3 and Glavind and Attström had people undertake a detailed oral examination of their own mouth using toothpicks, toothbrush and a mouth mirror together with a manual of instructions and intra-oral photographs to determine indicators such as mobility, migration, bleeding and gum colour.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Research suggests that certain self-reported dental information is valid. The validity of self-reports of tooth counts and presence of removable dentures has generally been high, [10][11][12][13] although validity varies with the degree of specificity required. Self-reported utilization of dental care has also been found to be valid, but this validity also varies with the level of specificity required (e.g., frequency of dental visits, types of services received, reasons for care).…”
mentioning
confidence: 99%
“…Self-reported utilization of dental care has also been found to be valid, but this validity also varies with the level of specificity required (e.g., frequency of dental visits, types of services received, reasons for care). 10,[14][15][16][17] To our knowledge, no prospective study of the validity of self-reported use of specific types of dental services has been reported. We describe here the results of such a study.…”
mentioning
confidence: 99%